Accounting for gender differences in the distributional effects of tax and benefit policy changes - Silvia Avram; Daria Popova; Olga Rastrigina (University of Essex, Institute for Social and Economic Research (ISER), 2016)
The distributional impact of policy changes is usually considered in terms of equivalised household income, assuming that each individual within the household is being affected in the same way, as a result of complete income pooling. The aim of this paper is to extend this approach by introducing a gender perspective in the analysis of policy effects. We use EUROMOD, the tax-benefit microsimulation model for the EU, to estimate the effects of changes in tax-benefit policies over the period 2008-2014 separately for men and women. The paper consists of two parts. First, we apply the standard approach based on the equal income sharing assumption but focus on lone parent families - a specific household type which makes gendered policy effects easier to observe. This analysis is performed for 18 EU countries: Belgium, Bulgaria, the Czech Republic, Denmark, Germany, Estonia, Ireland, Spain, France, Italy, Latvia, Luxembourg, Hungary, the Netherlands, Poland, Romania, Finland and Sweden. Second, we estimate the policy effects for men and women in couples. To obtain gender specific effects, we redefine income at the individual level by allocating income components to each adult within the household according to a set of assumptions. We present three alternative scenarios of intra-household income sharing. All scenarios assume that all individual incomes (e.g. earnings, individual benefits) are retained by their recipients, while common incomes (e.g. family benefits, housing allowances) are distributed following three different sets of sharing rules, which are defined in relation to the primary and the secondary earner status. We compare the outcomes of men and women in these three scenarios and in the baseline which assumes equal income sharing. This analysis is performed for six countries which differ in terms of the degree of defamilialisation their welfare regimes provide: Belgium, the Czech Republic, Spain, France, Romania and Finland.
Keywords: D13; H23; I32; 330; Tax-benefit policies; Microsimulation; Gender; Intra-household income sharing; European Union